Proceedings of the Institute of Industrial Engineers Asian Conference 2013 - Lin, Yi-Kuei.; Tsao, Yu-Chung.; Lin, Shi-Woei.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2013)
This book is based on the research papers presented during The Institute of Industrial Engineers Asian Conference 2013 held at Taipei in July 2013. It presents information on the most recent and relevant research, theories and practices in industrial and systems engineering. Key topics include: Engineering and Technology Management Engineering Economy and Cost Analysis Engineering Education and Training Facilities Planning and Management Global Manufacturing and Management Human Factors Industrial & Systems Engineering Education Information Processing and Engineering Intelligent Systems Manufacturing Systems Operations Research Production Planning and Control Project Management Quality Control and Management Reliability and Maintenance Engineering Safety, Security and Risk Management Supply Chain Management Systems Modeling and Simulation Large scale complex systems.
Engineering and Technology Management -- Engineering Economy and Cost Analysis -- Engineering Education and Training -- Facilities Planning and Management -- Global Manufacturing and Management -- Human Factors -- Industrial & Systems Engineering Education -- Information Processing and Engineering -- Intelligent Systems -- Manufacturing Systems -- Operations Research -- Production Planning and Control -- Project Management -- Quality Control and Management -- Reliability and Maintenance Engineering -- Safety, Security and Risk Management -- Supply Chain Management -- Systems Modeling and Simulation -- Large scale complex systems.
Keywords: Engineering; Engineering economics; Engineering economy; Manufacturing industries; Machines; Tools; Quality control; Reliability; Industrial safety; Industrial engineering; Engineering; Engineering Economics, Organization, Logistics, Marketing; Manufacturing, Machines, Tools; Quality Control, Reliability, Safety and Risk; Operating Procedures, Materials Treatment; Electronic books